Leveraging Applications of Formal Methods, Verification and Validation: 10th International Symposium on Leveraging Applications of Formal Methods, ISoLA 2021, Rhodes, Greece, October 17-29, 2021, Proceedings - Margaria, Tiziana; Steffen, Bernhard (Lecture Notes in Computer Science, 2021)
This book constitutes contributions of the ISoLA 2021 associated events. Altogether, ISoLA 2021 comprises contributions from the proceedings originally foreseen for ISoLA 2020 collected in 4 volumes, LNCS 12476: Verification Principles, LNCS 12477: Engineering Principles, LNCS 12478: Applications, and LNCS 12479: Tools and Trends. The contributions included in this volume were organized in the following topical sections: 6th International School on Tool-Based Rigorous Engineering of Software Systems; Industrial Track; Programming: What is Next; Software Verification Tools; Rigorous Engineering of Collective Adaptive Systems.